The Subjective Narrativisation of fait-divers. From Carrère to Luzzatto (Altre Modernità, 2025)
In L'Adversaire (2000), Emmanuel Carrère reconstructs the story of the murderer Jean-Claude Romand, inserting himself into the narrative as a character who explores and seeks to understand the events, questioning his own feelings and empathetic involvement. This is a long-contemplated narrative operation, conceived as a reaction to Truman Capote's stylistic choice in In Cold Blood (1966) and interpreted as an act that problematizes reportage and responds to the anxiety of derealisation of contemporary literature (Donnarumma: 2014). More than twenty years later, the subjective account proposed by Carrère has become a mannerism, defining a true topos of contemporary non-fiction. This approach is explicitly replicated in El impostor (2014) by Javier Cercas and in Max Fox o le relazioni pericolose (2019) by Sergio Luzzatto. Through textual analysis, this contribution aims to reconstruct how the narrative strategies exemplified in L'Adversaire end up constituting a repertoire of techniques that Cercas still tries to discuss, and from which Luzzatto draws almost automatically, asserting an ideal and risky aesthetic autonomy.
Keywords: fait-divers; non-fiction; Carrère; Cercas; Luzzatto; repertoire